Corruption: an overview about causal factors of the empirical studies across countries (Research, Society and Development, 2021)
This research aims to identify the main evidence found by empirical research on the conceptualization, measurement and causes of corruption. Thus, a qualitative meta-analysis of empirical studies on corruption was carried out, considering three dimensions: its causal factors, its definition and measurement indices. As a result, convergences and peculiarities about the theme were identified in scientific production, indicating an evolution and maturation in the understanding of the conception of corruption. In the studies analyzed, the causal factors of corruption identified as significant are the political, social, cultural, economic and legal factors of a society.